2019
DOI: 10.3390/s19173661
|View full text |Cite
|
Sign up to set email alerts
|

Dancing Salsa with Machines—Filling the Gap of Dancing Learning Solutions

Abstract: Dancing is an activity that positively enhances the mood of people that consists of feeling the music and expressing it in rhythmic movements with the body. Learning how to dance can be challenging because it requires proper coordination and understanding of rhythm and beat. In this paper, we present the first implementation of the Dancing Coach (DC), a generic system designed to support the practice of dancing steps, which in its current state supports the practice of basic salsa dancing steps. However, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Sensors are increasingly becoming portable and smarter, enabling efficient methods for the acquisition of performance data, which allows for effective monitoring and intervention. Such sensors have been explored to provide support in various learning domain [8,15,[17][18][19]. Schneider et al [20] analysed 82 prototypes found in literature studies based on Bloom's taxonomy of learning domains and explored how they can be used to provide formative assessment, especially as a feedback tool.…”
Section: Sensors In Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors are increasingly becoming portable and smarter, enabling efficient methods for the acquisition of performance data, which allows for effective monitoring and intervention. Such sensors have been explored to provide support in various learning domain [8,15,[17][18][19]. Schneider et al [20] analysed 82 prototypes found in literature studies based on Bloom's taxonomy of learning domains and explored how they can be used to provide formative assessment, especially as a feedback tool.…”
Section: Sensors In Sportsmentioning
confidence: 99%
“…Data from smartphones have been used to predict human activities such as movement [ 10 , 11 ] and fall detection [ 12 ]. Another external sensor used for training psychomotor skills is Microsoft Kinect [ 13 , 14 , 15 ]. The Kinect is an external infrared sensor that is used to track skeletal points of the human body and their movements, which can also be useful in the case of table tennis.…”
Section: Introductionmentioning
confidence: 99%
“…All decisions obtained in this comparison are presented in Table 7 on the basis of both Expert System (with system warnings) and trainer. In order to facilitate the procedures, good and moderate movements of the participants in the trainer evaluations were accepted as the correct movements as in [88,89]. In Table 7, the decisions taken by the system are matched by the decisions of the trainer by 89% in DSP training, 82% in LR training, and 85.5% in total.…”
Section: Decisions Of Rule-based Expert Systemmentioning
confidence: 99%
“…Dancing, which consists of feeling the music and expressing it in rhythmic movements of the body, is an activity that positively enhances the mood of people. In paper [13], Romano et al present the first implementation of the Dancing Coach (DC), a generic system designed to support the practice of dancing steps which, in its current state, supports the practice of basic salsa dancing steps. Results from the user test show that participants stated they had learned the basic salsa dancing steps, allowing them to move to the beat and use body coordination in a fun way.…”
Section: Contributionsmentioning
confidence: 99%